Type and Density of Zooplankton in The Tepian Batu Lake Teratak Buluh Village, Siak Hulu Sub Distriet, Kampar District, Riau Province - Lauri Sahat Parulian M; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThere were several human activities around the Tepian Batu Lake which contrubuted input of organic and anorganic matter and thus influence the type and density of zooplankton. To understand the types and density of zooplankton in the Tepian Batu Lake, a research has been carried out in June-July 2019. There were three sampling points, namely in the inlet, in the middle of the lake, and in the end of the lake. In cach sampling points, the water was sampled from the surface and 2 Secchi depth. Sampling were conducted 3 times, once/week. Water quality parameters measured were temperature, dissolved oxygen, transparency, pH, nitrate and phosphate. Results shown that there were 15 species of zooplankton present and they were belonged to 8 classes, namely Cladocera (1 species), Monogononta (3 species), Crustacea (2 species), Copepoda (2 species), Ciliata (3 species), Sarcodina (1 species), Protozoa (2 species), dan Sagittoeida (1 species). The zooplankton average density in the Tepian Batu Lake was 2160-4410 organisms/L. The most common type of zooplankton present in the Tepian Batu Lake was Ciliate. Water quality parameter values were as follow, temperature was 28.7-30.5 oC, transparency was 56.5-63.75 cm, dissolved oxygen was 3.13-5.35 mg/L, pH was  5-5.25, CO2 was 6-12,99 mg/L, nitrate was 0.031-0.078 mg/L, and phosphate was 0.062-0.116 mg/L. Based on the type of zooplankton present, it can be concluded that the Tepian Batu Lake can be categorized as oligotrophic.Keywords : Kampar River, Oxbow Lake, Water quality